2017
DOI: 10.1021/acs.macromol.7b01173
|View full text |Cite
|
Sign up to set email alerts
|

Self-Accelerating Click Reaction in Step Polymerization

Abstract: A self-accelerating double-strain-promoted azide−alkyne cycloaddition reaction (DSPAAC) was used in the step polymerization for the first time. This produced a novel stoichiometric imbalance-promoted homogeneous step polymerization method using sym-dibenzo-1,5-cyclooctadiene-3,7-diyne (DIBOD) and various bis-azide compounds (N 3 -R-N 3 ) as respective monomers. Because of the self-accelerating property of DSPAAC reaction, the novel step polymerization method could prepare high molecular weight polymers under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…To construct hyperbranched multicyclic polymer, selecting a proper A 2 monomer is of great importance in order to achieve a high molecular weight. In recent years, Zhang et al reported self‐accelerating double‐strain‐promoted azide−alkyne cycloaddition reaction (DSPAAC) to prepare cyclic polymers and periodic polymers . In this reaction, a commercially available chemical, sym ‐dibenzo‐1,5‐cyclooctadiene‐3,7‐diyne (DBA) was used, and it revealed an interesting chemical property, that is, once the cycloaddition of the first alkyne of DBA with azide occurred, the reactivity of the second alkyne would be enhanced significantly due to the increased ring strain of DBA.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To construct hyperbranched multicyclic polymer, selecting a proper A 2 monomer is of great importance in order to achieve a high molecular weight. In recent years, Zhang et al reported self‐accelerating double‐strain‐promoted azide−alkyne cycloaddition reaction (DSPAAC) to prepare cyclic polymers and periodic polymers . In this reaction, a commercially available chemical, sym ‐dibenzo‐1,5‐cyclooctadiene‐3,7‐diyne (DBA) was used, and it revealed an interesting chemical property, that is, once the cycloaddition of the first alkyne of DBA with azide occurred, the reactivity of the second alkyne would be enhanced significantly due to the increased ring strain of DBA.…”
Section: Methodsmentioning
confidence: 99%
“…In this reaction, a commercially available chemical, sym ‐dibenzo‐1,5‐cyclooctadiene‐3,7‐diyne (DBA) was used, and it revealed an interesting chemical property, that is, once the cycloaddition of the first alkyne of DBA with azide occurred, the reactivity of the second alkyne would be enhanced significantly due to the increased ring strain of DBA. When this type of A 2 monomer is used in polycondensation, a high molecular weight of the resultant polymer can be realized even in a stoichiometric imbalance condition . Thus, the polymerization of DBA and c‐PS was conducted in THF, and the detailed reaction condition is given in Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[20][21][22][23][24][25][26][27][28] This feature was successfully applied to the synthesis of cyclic polymers and stepgrowth polymerization. [29,30] However, due to the very fast reaction, the regiochemistry of the bis-triazole products (2a and 2b) was not totally controlled.…”
Section: Introductionmentioning
confidence: 99%